Alternative PSS Business Models of ESCO: Towards an Innovative New Model - Eka Sudarmaji; Noer Azam Achsani; Yandra Arkeman; Idqan Fahmi (School of Business, IPB University (SB-IPB), 2021)
Product System Service (PSS) was an excellent way to create new customer value under hyper-competition. Both product and service components were not used individually but in integrating product, service, and system and their valid combinations. This paper investigated the case study and was performed between June 2019 and April 2020. The is study aims to explore the introduction of the study's purpose of exploring the company was introducing the latest PSS model in its own